2011
DOI: 10.1111/j.1750-3841.2011.02395.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant Activity of Different Cultivars of Banana Flower (Musa paradicicus L.) Extracts Available in India

Abstract: Six different cultivars of banana flowers (Musa paradicicus) (Kathali, Bichi, Shingapuri, Kacha, Champa, and Kalabou) were analyzed for the content of polyphenol expressed as gallic acid equivalent and flavonoid expressed as quercetein equivalent, and the in vitro total antioxidative activities of the flower extracts were compared with standard and expressed as trolox equivalent. The reducing power, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…). The observed functional groups are the constituent parts of polyphenols, flavonoids, anthocyanins, dopamines, serotonin in the MBLE . Considerable shifts in the peaks were detected at 3349, 3266, 1780, 1649, 1485, 1248 and 1081 cm −1 in the spectra after MGNs formation.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…). The observed functional groups are the constituent parts of polyphenols, flavonoids, anthocyanins, dopamines, serotonin in the MBLE . Considerable shifts in the peaks were detected at 3349, 3266, 1780, 1649, 1485, 1248 and 1081 cm −1 in the spectra after MGNs formation.…”
Section: Resultsmentioning
confidence: 87%
“…M. balbisiana is cultivated in more than 135 countries such as tropical Indomalaya, Australia, Papua New Guinea or India . Previously reported, aqueous M. balbisiana leaf extract (MBLE) contains polyphenols, flavonoids, minerals, anthocyanins, serotonin, dopamines . The M. balbisiana leaf is traditionally known as a natural antidote as it can reduce the effects of poisons from bee stings, spider bites, insect bites, plus rashes, skin irritation, minor skin wounds and in addition treat skin disorders such as dandruff, sunburn and eczema etc.…”
Section: Introductionmentioning
confidence: 99%
“…Outer leaf sheaths of pseudostem of cultivars nendran, robusta and kathali exhibited total phenolics of 110, 94 and 79 mg GAE/g of extract, respectively and total flavonoids of 49, 38 and 27 mg QE/g of extract, respectively (Anusuya, Gomathi, Tharani, & Murugesan, 2013). Phenolic and flavonoid content of flower from six different banana cultivars ranged from 2.14 to 11.94 mg GAE and 0.023 to 0.174 mg QE/g of dry weight (China et al, 2011). In our earlier study, the polyphenolic content of pseudostem of eight different banana cultivars revealed that the TPC and TFC ranged from 7.58 to 291 mg GAE and 4 to 80 mg CE/g of extract (Saravanan & Aradhya, 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…Acetone extract exhibited high reducing power with lowest EC 50 value of 6.5 mg/mL followed by methanol (21 mg/mL) and chloroform (90 mg/mL) ( Table 3). The activity was observed to be higher than the reducing power of juice from banana rhizome and pseudostem (Saravanan & Aradhya, 2011a), and also flower from different banana cultivars (China et al, 2011). The reducing power capacity of a BR extracts may serve as a significant indicator of antioxidant property by donates electrons to reactive free radicals species, thus promoting the termination of free radical chain reactions.…”
Section: Total Reducing Power (Trp) Assaymentioning
confidence: 97%
“…flower and pseudostem extracts. China et al, (2011) reported that, the banana flowers are a potential source of natural anti-oxidants.…”
Section: Introductionmentioning
confidence: 99%